Sintesis Kromium Ferit Dari Pasir Pantai dan Karakterisasi Awal Sensor Suhu - Widya Elyani; Arif Hidayat; Ahmad Taufiq; Sunaryono Sunaryono (Universitas Negeri Malang, 2018)
Ferrofluids for temperature sensor application become one of the important modern technology applications. Therefore, the development of the beach sand-based ferrofluids for temperature sensor becomes new and essential things for cutting off their production. In this research, the preliminary investigation of the temperature sensor is developed based on the chromium ferrite ferrofluids. The sample in powder and fluid were prepared by coprecipitation-sonochemical technique. The powder sample which was characterized by XRD has the crystallite size of 10 nm with high purity. The preliminary investigation shows that the chromium ferrite ferrofluid has a good property as a candidate for temperature sensor application showing a good response on the temperature treatmentDOI: http://dx.doi.org/10.17977/um024v3i12018p001